Systemic treatment of non-small cell lung cancer brain metastases - Cedrych, Ida; Kruczała, Maksymilian A.; Walasek, Tomasz; Jakubowicz, Jerzy; Blecharz, Paweł; Reinfuss, Marian (Contemporary Oncology/Współczesna Onkologia, 2016)
In the systemic treatment of brain metastases from non-small cell lung cancer (BMF-NSCLC) chemo- and targeted therapy are used. Response rates after platinum-based chemotherapy, range from 23% to 45%. Development of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs): gefitinib or erlotinib, was an improvement in treatment of advanced NSCLC patients. EGFR mutations are present in 10–25% of NSCLC (mostly adenocarcinoma), and up to 55% in never-smoking women of East Asian descent. In the non-selected group of patients with BMF-NSCLC, the overall response rates after gefitinib or erlotinib treatment range from 10% to 38%, and the duration of response ranges from 9 to 13.5 months. In the case of present activating EGFR mutation, the response rate after EGRF-TKIs is greater than 50%, and in selected groups (adenocarcinoma, patients of Asian descent, never-smokers, asymptomatic BMF-NSCLC) even 70%. Gefitinib or erlotinib treatment improves survival of BMF-NSCLC patients with EGFR mutation in comparison to cases without the presence of this mutation. There is no data on the activity of the anti-EML4-ALK agent crizotinib. Bevacizumab, recombinant humanised monoclonal antibody anti-VEGF, in the treatment of advanced non-squamous NSCLC patients is a subject of intense research. Data from a clinical trial enrolling patients with pretreated or occult BMF-NSCLC proved that the addition of bevacizumab to various chemotherapy agents or erlotinib is a safe and efficient treatment, associated with a low incidence of CSN haemorrhages. However, the efficacy and safety of bevacizumab used for therapeutic intent, regarding active brain metastases is unknown.